Study protocol of the METAPANC trial - intensified treatment in patients with local operable but oligometastatic pancreatic cancer - multimodal surgical treatment versus chemotherapy alone: a randomized controlled trial - Michael Ghadimi; Uwe Pelzer; Marc G. Besselink; Jens Siveke; Ralph Telgmann; Rickmer Braren; Hanneke Wilmink; Marie Crede; Alexander Koenig; Ute Koenig; Sven Thorsten Liffers; Kai Antweiler; et al. (BMC Cancer)
Abstract Background Based on current guidelines, surgical treatment of hepatic oligometastases in patients with pancreatic ductal adenocarcinoma (PDAC) is not primarily recommended. Systematic chemotherapy is the therapy of choice for these patients. The relevance of subsequent surgical resection after chemotherapy remains unclear. This multicentre, randomized, controlled phase III trial is planned to evaluate whether resection of the primary tumor and liver metastases can improve overall survival in patients with PDAC with hepatic oligometastases in a multimodal treatment setting. Methods After an induction therapy with eight cyles of mFOLFIRINOX and a response assessment after four and eight cycles, patients will be randomized to either Arm 1 (perioperative mFOFIRINOX plus resection of the primary tumor with resection or ablation of all hepatic metastases) or Arm 2 (continuation of 4 cycles of the standard-of-care mFOLFIRINOX chemotherapy). This clinical trial will focus on a well-defined patient group with metastatic disease limited to the liver as the target organ, with a maximum of three metastases. Discussion METAPANC is the first international, randomized, controlled, open-label, multicentre, phase III clinical trial for curative intended surgical therapy of oligometastatic pancreatic cancer in Europe and America. The multimodal surgical treatment of patients with oligometastatic pancreatic cancer could significantly extend the overall survival of this patient group. A possible recommendation of this multimodal treatment regimen outside of clinical trials requires data from randomized controlled trials first. To identify patient subgroups that might benefit from multimodal surgical therapy, additional information on tumor genetics could supplement valid parameters. Trial registration EU Clinical Trials No. 2023-503558-10-00.